Concrete Beams Strengthened with Jute Fibers - Yaseen Ali Salih; Nadia Nazhat Sabeeh; Mohammed Faeq Yass; Ahmed Shihab Ahmed; Ektiffa Saleh Khudhurr (Salehan Institute of Higher Education, 2019)
Nowadays, the reinforcement of concrete with natural fibers can consider being an effectual scheme to achieve the global demand for sustainable development. Due to sustainability, bio degradability, and environmental friendly, natural fibers are preferred as compared to synthetic fibers. The present study investigated the effect of width and thickness of jute fiber strips on the mechanical properties of reinforced concrete beams (RC beams). The experimental program consisted testing of twenty-four RC beams (150*150*1000 mm) comprised of four groups. The first group consisted of three reference RC beams, the second group consisted of three RC beams strengthened longitudinally with carbon fiber strip (CFRP) of 15 cm width, the third group included nine RC beams strengthened longitudinally with one layer of jute fiber strips (JFRP) having variable width, 5, 10, and 15 cm, and lastly the fourth group which was same as the third group except using double layer of jute fiber strips. Generally, the results showed that toughness, ultimate flexural strength, and load carrying capacity of RC beams strengthened with JFRP were increased with the increase of the strip width and thickness. On the other hand, ductility and stiffness were decreased with the increase of the strip width. Test results showed that load carrying capacity was improved by 5.56 and 11.1% for one layer of jute fiber strips of 5 and 15 cm width respectively as compared with the reference specimens. On the other hand, the load carrying capacity was improved by 3.95 and 8.75 % for two layers of jute fiber strips of 10 and 15 cm width respectively as compared with the one layer strengthened specimens. Concerning the CFRP strengthening, the load carrying capacity was improved by 77.76% as compared with the reference specimens.